THE NURSING STUDENTS NEED OF LEARNING MEDIA FOR LEARNING ENGLISH - Desi Rochmawati (Universitas Putera Batam, 2020)
English language is frequently taught in Indonesian vocational college such as in Nursing Department. It is such a challenge for the students and the lecturer as well due to the tight schedule. The students need more exposures in English language, but the English course so far is only taught conventionally in the classroom once in a week for 2 semesters. The students need to fulfill certain competence in English in effective ways, one of the competence is English speaking skill. Learning speaking needs more effective methods. The methods could be in the form of the media used in teaching learning process. Besides, English speaking skill was so urgent for the students both in academic affair and professionalism. This study, therefore, observes the students’ need of learning media for learning English speaking. This was a qualitative research by conducting a syllabus investigation, interview, and questionnaire to collect the qualitative research data. The quantitative data was also conducted through delivering questionnaires to add the meaning of the qualitative data. This study revealed the kinds of learning media that the students need in learning English speaking skills that would also help them easily get the English courses exposures. The appropriate learning media for learning English speaking was a mobile learning media which has portability and high connectivity. It was a kind digital learning media that can be accessed at anytime and anywhere, installed in their smartphones which consisted of some speaking activities and their supporting activities.